Analisis Portofolio Produk-Pasar untuk Mengembangkan Perencanaan Pasar Strategis pada Perusahaan Jasa Logistics - Sudrajat, Darjat (Bina Nusantara University, 2011)
Generally, companies will get continuous success because they have commitment towards strategic market planning, where they continuously auditing work performance, exploring cost decision, and investing to the balance improvement in short and long term and looking for new chances. Therefore, the suitable strategic marketing planning for companies are offensive type by invest to grow and defensive way by protecting position. However, in protecting market share, a company could invest to protect their position in developing market, to protect one high share, to protect one follower share position, and to protect one niche position.Â